(Re)inventing african oral traditions and national heritage[s] through film images: the case of Keita! The heritage of the Griot [1995] and Kare kare zvako: Mother’s day [2004] - Rwafa, Urther (Taylor & Francis (Routledge, 2016)
The aim of this article is to explore how African films such as Keita! The Heritage of the Griot and Kare Kare Zvako: Mother’s Day reinvent oral traditions on-screen, so that the traditions are revitalised and given new life in a contemporary world where visual and literary narratives have tended to dominate the collection and dissemination of information. The ontological and cosmological dimensions of African oral traditions provide the cultural humus that continues to feed the narrative structures of most African films. It is argued that the films’ conscious refusal to be totally submerged in European modernism or their capacity to merge some traditional aspects with modern values is what constructs the multiple subjectivities that most African filmmakers strive to bring out. By using oral narrative structures embedded in songs, storytelling, myths, legends, poems, riddles, anecdotes and proverbs, the selected African films recreate traditions and heritage; they help to preserve African values that face a Western onslaught, promoted through European languages. Oral narratives carry a freight of cultural meanings infused in different modes of expression, while articulating the philosophies and beliefs of African people. It is important to recognise and [re]discover the critical role played by oral narratives in order to understand the epistemologies and ontologies that inform the construction of African films. A study of this nature is critical in that it builds on the existing indigenous knowledge systems embedded in orature (oral literature) that remain threatened by European cultural imperialism, which is promoted through the Hollywood film paradigm.